To Determine the Vertical Transmission Rate of HIV in the PPTCT Programme since its Initiation in 2005 in Umaid Hospital, Jodhpur (Rajasthan) - Khokher, Santosh; Kumar Dhaka, Vinod; Singh, H.V. (Asian Journal of Medical Research, 2019)
Background: As a part of the PPTCT program by NACO, the PPTCT program was started in our institute in April 2005. So this study is planned to note the vertical transmission rate of HIV in the PPTCT program as well as to have an evaluation of the PPTCT program in our institute since the initiation of this programme in 2005. Subjects and Methods: The present study was carried out in the department of Obsteterics and Gynaecology, Umaind Hospital attached to Dr. S. N. Medical College, Jodhpur. The data over this period were analyzed. As per the strategy and policy prescribed by NACO, tests (E/R/S) were performed on the serum samples. Those found HIV positive went for confidential post-test information and counseling regarding through intimation about the vertical transmission and importance of their institutional deliveries. Results: The present study shows that 29.82% of the seropositive women had anemia 26.31 had deranged LFT, 36.84% had genital infections. Mostly 99.18% new born were given Neviraoine. We found that 10 seropositive mothers had puerperial pyrexia, 8 had mastitis, 6 had UTI, 1 had episiotomy gap and another 1 had wound sepsis or gaping in LSCS wound. Conclusion: Prevention is the cure and antenatal clinic is the best opportunity to educate so simple intervention strategies under this PPTCT program will reduce the incidence of pediatric HIV infection in our scenario.